Effect of Levo-Carnosine Co-Administration On Cisplatin-Induced Portal Inflammation And Fibrosis Of The Liver In BALB/c Mice - Bashir, Sumyyia; Qamar, Khadija; Ali, Sajid; Faisal, Tayyaba; Khalid, Rabya; Zahid, Aqsa (Journal of Rawalpindi Medical College, 2026)
Objective: To investigate the effect of levo-carnosine co-administration on portal inflammation and fibrotic alterations caused by cisplatin in the BALB/c mice liver. Methods: The study was carried out from December 2020 to April 2022 at the Department of Anatomy in collaboration with the Department of Physiology, Army Medical College in Rawalpindi. The study included 90 adult BALB/c mice; three groups of 30 mice each. Group A (Control) was not given any medication. Group B (Cisplatin) received intraperitoneal cisplatin 8mg/kg body weight as a single weekly dose for four weeks, whereas Group C (Carnosine + Cisplatin) administered similar cisplatin treatment along with levo-carnosine 300mg/kg body weight every day by oral lavage. Mice were then euthanized, a 2 ml of terminal blood sample was obtained by intracardiac puncture for biochemical analysis, and then the liver was dissected out, processed, and stained with Hematoxylin and Eosin (H&E) and Masson’s trichrome stains to study portal inflammation and fibrosis, respectively. Results: Absence of portal inflammation was observed in 86.7% of mice in group A, moderate to severe portal inflammation was seen in 66.7% specimens in group B, whereas mild portal inflammation was observed in 43.3% of specimens in group C. Group B shows significantly (p<0.001) raised portal inflammation among the three groups. Similarly, liver fibrosis was not seen in 93.3% of mice in group A, mild to moderate fibrosis was seen in 83.3% specimens in group B, whereas mild fibrosis was noted in 26.7% of mice in group C. Group-C shows significantly (p<0.001) high liver fibrosis among the three groups. The serum albumin mean was 2.36±0.12 g/dl, 1.71±0.12 g/dl, and 2.16±0.26 g/dl in group A, group B, and group C, respectively. A significant (p<0.001) decrease in serum albumin was observed in group B when associated with group A and group C. Conclusion: Cisplatin administration caused portal inflammation and fibrosis in the liver of mice. Levo-carnosine, when administered along with cisplatin, reduced the toxic effect of cisplatin on the mice's liver. Keywords: Antioxidants, Carnosine; Cisplatin; Inflammation; Liver disease.